Pengendalian Kualitas terhadap Critical Processes pada Hanger Line Proses Sewing di PT. XYZ Menggunakan Metoda FMEA dan FTA - Eko Setiawan; Desy Evi Oktaviana (Program Studi Teknik Industri Universitas Setia Budi, 2023)
Observation to critical processes at the hanger line of sewing process in PT. XYZ .found that there were defect and repair products. This research aims to controlling the quality of the critical processes in such away that the defect and repair products be minimized. The Failure Mode and Effect Analysis (FMEA) is applied to prioritize the defect types. Root causes of the defects are obtained by applying the Fault Tree Analysis (FTA), leading to the improvement proposal. The research found that Inconsistent welt pocket (RPN value 100) and imbalanced collar (RPN value 84) as the causes with the two highest risks. Proposed improvements proposed for these causes are the leveling of the panel in the acrylic; the need to make sure that the acrylic used is in accordance with the style being produced; the need for supervision to monitor the performance of the operators; the need for counseling for the operators; the need to make sure that the back body and the front body equal and match the approved sample; the need to make sure that the collar size fits and matches the approved sample; and the provision of pattern styles as references for the operators.